2010
DOI: 10.1071/sr10009
|View full text |Cite
|
Sign up to set email alerts
|

An investigation into the reactions of biochar in soil

Abstract: Abstract.Interactions between biochar, soil, microbes, and plant roots may occur within a short period of time after application to the soil. The extent, rates, and implications of these interactions, however, are far from understood. This review describes the properties of biochars and suggests possible reactions that may occur after the addition of biochars to soil. These include dissolution-precipitation, adsorption-desorption, acid-base, and redox reactions. Attention is given to reactions occurring within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
518
1
14

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 912 publications
(557 citation statements)
references
References 64 publications
24
518
1
14
Order By: Relevance
“…On the other hand, the values of FTIR spectra of SSHB (Table 3) showed the bands located at 3419, 2351, 1581, 1391 and 830 cm -1 , which correspond mainly to the presence of N-H, stretched O-H (hydroxyl), -NH (amine), asymmetric C-H, and aromatic C-C 2+ removal by SSHB may reflect dissimilarity in retention mechanisms followed by biochar and those pursued by feedstock and active carbon. According to the metal ion adsorption by surface-active materials, Cu 2+ removal can be achieved by electrostatic interaction with negatively charged surface functional groups (cation exchange), specific metal-ligand complexation involving surface functional groups of biosorbents, interactions between metals and aromatic C of biosorbents and/or physical sorption controlled by surface area and porosity (Biniak et al 1997;Joseph et al 2010;Uchimiya et al 2010). Significant changes in pH values were observed with the progress of removal reactions (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the values of FTIR spectra of SSHB (Table 3) showed the bands located at 3419, 2351, 1581, 1391 and 830 cm -1 , which correspond mainly to the presence of N-H, stretched O-H (hydroxyl), -NH (amine), asymmetric C-H, and aromatic C-C 2+ removal by SSHB may reflect dissimilarity in retention mechanisms followed by biochar and those pursued by feedstock and active carbon. According to the metal ion adsorption by surface-active materials, Cu 2+ removal can be achieved by electrostatic interaction with negatively charged surface functional groups (cation exchange), specific metal-ligand complexation involving surface functional groups of biosorbents, interactions between metals and aromatic C of biosorbents and/or physical sorption controlled by surface area and porosity (Biniak et al 1997;Joseph et al 2010;Uchimiya et al 2010). Significant changes in pH values were observed with the progress of removal reactions (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…There is growing recognition that unless biophysical drivers are explicitly considered, we will not be able to estimate the consequences of land-use changes on soil C stocks (15) or predict the effects of management decisions, such as biochar amendment, to increase carbon sequestration (16). Precipitation strongly influences plant production, fluxes of soil C pools, and ultimately total soil C stocks and residence time (1).…”
Section: Discussionmentioning
confidence: 99%
“…Differential response to PTs showed that at low PT (<400ºC) BCs favour greater recovery of C and other nutrients (both macro and micro) compared with high PT (>400°C) BCs because these nutrients are increasingly lost at higher PTs. In addition, low PT BCs have faster and greater soil activity, and thus contribute more to soil fertility (Joseph et al, 2010).…”
Section: Referencesmentioning
confidence: 99%